PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS PROBLEM BASED LEARNING PADA MATERI BILANGAN DI KELAS VII SMP NEGERI 22 KOTA JAMBI - . relawati (Jurnal Ilmiah Dikdaya, 2017)
This research is based on the sample of the problem on the Student Worksheet (LKS) is still lack of structured steps of work, the exercise problem is not related to everyday life. This research is a development research. Products developed in the form of Student Worksheet (LKS) mathematics on the number material for SMP class VII with problem based learning model. The development model used is the ADDIE model consists of several stages: Analyze, Design, Development, Implementation, and Evaluation. Validation was done by 2 material experts, design experts and media experts. The Student Working Sheet (LKS) developed was tested in 3 stages, one to one learner with 3 subjects, small group trials (small Group try-out) with the subject of 6 students, field trials (field try-out) with the subject of 36 students. The results showed that the Student Worksheet (LKS) problem based on problem based learning based on the assessment: 1) material experts obtained The average total of 3.98 is included in the "Good" category and if it gets 80% it is included in the "Valid" category. 2) design experts obtained an average total of 4.00 which is included in the category of "Good" and if the percentage get the value of 80% so that included in the category "Valid". 3) the media expert obtained an average total of 4.83 which is included in the category of "Very Good" and if the percentage get 97% value so that included in the category of "Very Valid". The assessment by the students is done in 3 stages: 1) the individual test is obtained an average total of 4.55 which belongs to the category of "Very Good" and if the percentage get 91% value so that it is categorized as "Very Valid", 2) Average of 4.65 which is categorized as "Very Good" and if the percentage gets 93% so that it is categorized as "Very Valid", 3) the field trial obtained the average total 4,64 which belongs to the category of "Very Good" and if Censored 92% of the score so that it is categorized as "Very Valid". Thus, Student-Based Student Worksheet (LKS) based on problem based learning on the number material in class VII is declared valid and practical so feasible to be used in learning process by teacher and junior high student especially material number. Keywords: Student Worksheet Problem Based Learning